Electrical and Self-Sensing Properties of Alkali-Activated Slag Composite with Graphite Filler - Rovnaník, Pavel; Kusák, Ivo; Bayer, Patrik; Schmid, Pavel; Fiala, Lukáš (Materials (Basel, Switzerland), 2019)
The electrical properties of concrete are gaining their importance for the application in building construction. In this study, graphite powder was added to alkali-activated slag mortar as an electrically conductive filler in order to enhance the mortar's conductive properties. The amount of graphite ranged from 1% to 30% of the slag mass. The effect of the graphite powder on the resistivity, capacitance, mechanical properties, and microstructure of the composite was investigated. Selected mixtures were then used for the testing of self-sensing properties under compressive loading. The results show that the addition of an amount of graphite equal to up to 10% of the slag mass improved the electrical properties of the alkali-activated slag. Higher amounts of filler did not provide any further improvement in electrical properties at lower AC frequencies but caused a strong deterioration in mechanical properties. The best self-sensing properties were achieved for the mixture with 10 wt% of graphite, but only at low compressive stresses of up to 6 MPa.
Keywords: self-sensing; alkali-activated slag; microstructure; compressive strength; graphite; electrical resistivity